ACUPUNCTURE AND RELATED TECHNIQUES FOR POSTOPERATIVE PAIN : A SYSTEMATIC REVIEW - Sudartha Mantikei, Adrianus Nyoman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Eastern medicine has traditionally employed acupuncture to treat pain. Western medicine has increasingly embraced various types of acupuncture to manage pain. It relieves surgery pain. No study of acupuncture approaches used to alleviate surgery pain and their efficacy exists.Aim: This article explore about acupuncture and related techniques for postoperative pain. Methods: This study showed that it met all of the requirements by looking at the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. So, the experts could make sure that the study was as current as possible. The search method used a number of electronic reference databases, such as Pubmed and SagePub, to look for papers that were published between 2000 and 2023. We didn't look at review papers, articles that had already been published, or articles that were only half done. Result: In the PubMed database, the results of our search brought up 371 articles, whereas the results of our search on SagePub brought up 211 articles. The results of the search conducted for the last year of 2013 yielded a total of 152 articles for PubMed and 98 articles for SagePub. In the end, we compiled a total of 33 papers, 23 of which came from PubMed and 10 of which came from SagePub. We included eight research that met the criteria.Conclusion: Research shows the benefits of laser or electric acupuncture in reducing pain. This is indicated by the lower VAS level than controls and the need for analgesic use in post-abdominal surgery and neurosurgery patients. In addition, acupuncture provides minimal side effects.